Michael Adducts of 2-Methoxycarbonyl-1,4-benzoquinone with Different Donor Molecules - Ashnagar, A.; Bruce, J.M. (Asian Journal of Chemistry, 2010)
The main objective of the present work is the synthesis of Michael adducts from 2- methoxycarbonyl-1,4-benzoquinone as acceptor and malonitrile, p-cresol and thiophenol as donors, using a number of different bases such as 2-methoxypyridine, 4-dimethyl-aminopyridine, 1,5-diazabicy-clo[5.4.0]undec-5-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 18-crown- 6 + potassium fluoride. The results obtained had shown that the reactions of 2-methoxycarbonyl- 1,4-benzoquinone with the donor molecules and also the separation of the products were much more difficult than the corresponding reactions with 2-acetyl-1,4-benzoquinone. Spiro[4.1.2]hepta -1,3-diene and spiro[4.1.4]nona-1,3-diene were used in order to direct the Diels-Alder cycloaddition reaction (due to steric effect) to the unsubstituted side of 2-methoxycarbonyl-1,4-benzoquinone, but results had shown that a mixture of addition reaction to both sides of the benzoquinone were obtained.